Advances in Genetic Improvement of Legumes to Biotic Stresses - Sharma, Mamta; Tarfdar, Avijit; Ghosh, Raju; Rao, K. Mediga; Srinivas, K.; Varshney, Rajeev K. (Taylor & Francis Group, 2025)
The utility and demand of legumes are increasing unremittingly every year within the ever-growing populations especially within the vegetarian people over the world owing to its richness in proteins. However, biotic stresses are major factors in limiting legumes productivity especially in the Indian subcontinent and African continent. Global distribution and occurrence of various biotic stresses in legumes are well-documented. Among them, 50% of the diseases are caused by fungal pathogens and 38% by viral pathogens. Under changing climate scenario, various minor diseases are becoming major barriers in way for achieving high yields. Furthermore, the pathogens are becoming more aggressive. Resistant cultivars are widely recognized as the most efficient, safe, and economical method for management, and in the past few decades, a considerable care is being taken in legume protection strategies, and the production of legumes has increased magnificently, and disease-resistant varieties play a major role in that. In this chapter, we tried to collate the information about major diseases in legume crops, their worldwide distribution, and economic losses due to them. Some emerging challenges under changing climate have also been described including use of new tools and technologies that can play a key role in transforming legume-farming system for narrowing the yield gaps.